Characteristics of Co-operating Teachers - Clarke, Anthony (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In this large-scale study, I have profiled the backgrounds and assumptions of co-operating teachers. The results indicate that teachers have a high state of professional preparedness, a depth of experience not previously documented, an overwhelming desire for feedback, a strong call for selection criteria, and an unexpected gender difference in terms of numbers. The profile that emerged supports some common beliefs about co-operating teachers, refutes others, and extends an overall understanding of their involvement in teacher education. Most important, it signals a shift in the conception of their role within teacher education. L’article dresse le profil des antécédents et des postulats des enseignants associés. Les résultats indiquent que les enseignants sont très bien préparés, possèdent une vaste expérience, désirent connaître les réactions de leur entourage, s’intéressent aux critères de sélection et présentent une différence inattendue entre les sexes quant aux nombres. Le profil qui a émergé permet de mieux saisir le rôle des enseignants dans la formation des maîtres. Il signale surtout un changement dans la conception de leur travail : de superviseurs de stages, ils passent à celui de responsables de formation à l’enseignement.